Peran Perempuan dalam Perekonomian Keluarga Nelayan di Pesisir Utara Kabupaten Lamongan - Erly Juliyani (Program Studi Ekonomi Syariah dengan Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Institut Pesantren Sunan Drajat Lamongan, 2022)
Many women work in the fisheries trade sector because this sector is able to provide a regular source of income. Furthermore, the fisheries trade sector also provides a great opportunity for women's involvement because the work involved in the circulation of fish is very young and relates to the role of women. This Research focuses on the role of women in their work in the trade sector and whether the roles they build can create a bargaining position in decision-making in the family. Research was conducted in fish markets located in Kranji Village, Weru and Brondong, Lamongan. In the research, a descriptive qualitative approach was used, data were obtained using observation, interview, and documentation methods. Furthermore, the data was analyzed through several stages starting from data collection, data reduction, data presentation and conclusion drawing. Then data triangulation was carried out to test the validity of the data. The results show that the role of the fish trader women, who have an elusive sense of why they have to work, is very influential in improving the family economy. At the level of access and control, women have made advancement, although men's position still tends to be superior. To the same people, they have been interdependent and supported in their roles between husbands and wives